Strategi Komunikasi Pemasaran Produk UMKM ke Masyarakat di Era Digital melalui Media Sosial: Studi Kasus pada UMKM Rumah Mode Aqhita - Abdillah, Baihaqi; Saragih, M. Yoserizal; Abidin, Syahrul (Comit: Communication, Information and Technology Journal, 2024)
This research is entitled Communication Strategy for Marketing MSME Products to the Community in the Digital Era Through Social Media (Case Study on MSMEs Aqhita Fashion House). The purpose of this study is to find out how the strategies carried out by MSMEs in the digital era, especially what happened to the Aqhita Fashion House. This research uses qualitative research approaches and types, and the theory used is AISAS Theory (Attention, Interest, Search, Action, Share). The object of this research is the strategy of MSMEs in marketing their products to the public through social media. This research is where in this analys there are five elements in doing good marketing in the digital era, namely Attention, Interest, Search, Action, Share. The result of this study is to find out the right strategy in marketing MSME products in the digital era. The message that can be take in this study is that we can better appreciate the work made by humans and should not underestimate the results of products from MSMEs that are still relatively small.